Life of the Faculty of Military Education - Akbarov Anvar Tojimatovich; Ubaydullayev Saidakbar Saydalievich; Abduganiyev Jamhurbek Isroil o`g`li (Zien Journals, 2022)
This article is about the rector of Fergana State University and the head of the Faculty of Military Education I.Saidov and about the life of the University, and about 5 initiatives. And the intellectual tournament Zakovat was organized at Fergana State University
Keywords: Students; allowed; government; University